Efforts to Increase Motivation through the Baamboozle Platform in PJOK Learning - Titis Demokratis; Dinata, Vega Candra; Arifin, Zainal (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
Learning models that are less varied cause students to feel bored in participating in learning, by using an edugames learning model called baamboozle it is hoped that they will have high motivation in learning. The purpose of this research is to increase the learning motivation of students in grade 2 UPT SD Negeri 144 Gresik through the use of the baamboozle edugames learning platform. This study uses a Collaborative Classroom Action Research (PTK) design with the Kemmis & Taggart model. The research subjects were 20 grade 2 students of UPT SD Negeri 144 Gresik. Data was collected using observation and questionnaire techniques. Data analysis was carried out in a qualitative and quantitative descriptive manner. The use of the baamboozle edugames learning platform for PJOK subjects has increased student motivation. During the learning process, students are given access to the platform and formed into groups to work together as a team, which makes them more active and enthusiastic in learning. Before the action was taken, the percentage of students' learning motivation was still in the very poor category (54%). However, after the first cycle, there was a significant increase so that it rose to the sufficient category (74%). The final results show that students' motivation to learn PJOK is in a very good category (89%). The data analysis technique used to measure students' learning motivation is descriptive qualitative and quantitative.